Structural design, digital fabrication and construction of the cable-net and knitted formwork of the KnitCandela concrete shell. (June 2021) - Popescu, Mariana; Rippmann, Matthias; Liew, Andrew; Reiter, Lex; Flatt, Robert J.; Van Mele, Tom; Block, Philippe
Abstract: This paper describes the structural design, digital fabrication and construction of KnitCandela, a free-form, concrete waffle shell with KnitCrete, a falsework-less formwork approach using a custom prefabricated knitted textile as multi-functional, structural shuttering layer and a form-found cable net as the main load-bearing formwork. The digitally designed and fabricated textile provided integrated features for inserting and guiding elements such as cables and inflatables that helped shape the sophisticated mould. With a total weight of only 55 kg, the 50 m 2 formwork was easy and compact to transport. On site, the formwork was tensioned into a timber and steel rig, the pockets were inflated, and then coated with a thin layer of custom-developed, fast-setting cement paste. This paste served as a first stiffening layer for the textile, minimising the formwork's deformations during further concrete application. Fibre-reinforced concrete was manually applied onto the formwork to realise a 3 cm-thick shell with 4 cm-deep rib stiffeners. The novel approach, for the first time applied at architectural scale in this project, enables the building of bespoke, doubly-curved geometries in concrete, with a fast construction time and minimal waste, while also reducing the cost and labour of manufacturing complex parts.